2014
DOI: 10.1002/lary.24786
|View full text |Cite
|
Sign up to set email alerts
|

Modified robotic-assisted thyroidectomy: An initial experience with the retroauricular approach

Abstract: Single-incision retroauricular robotic hemithyroidectomy can be a safe and feasible alternative to other remote access techniques. Neck lift surgery can be performed safely in a select group of patients. However, future studies are warranted to further evaluate the benefits and limitations of this novel approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…Several studies have reported the safety of the retroauricular approach (12,(15)(16)(17)(18), and showed comparable complication rate to the conventional open approach (19). On the other hand, there are other risks specific to this approach, which is injury to the flap or GAN.…”
Section: Safety Of the Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported the safety of the retroauricular approach (12,(15)(16)(17)(18), and showed comparable complication rate to the conventional open approach (19). On the other hand, there are other risks specific to this approach, which is injury to the flap or GAN.…”
Section: Safety Of the Proceduresmentioning
confidence: 99%
“…The surgeons have to be aware of those risks during the procedure to prevent them, by careful dissection of the flap and identified and preservation of the nerve. However, it was reported that some patients develop temporary hypoesthesia at the surgery site or the area corresponding to the distribution of GAN, in spite of preserving the nerve, which improve spontaneously (12,15).…”
Section: Safety Of the Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Terris et al first described Robotic Retroauricular Thyroidectomy (RRT) in 2011, as 'robotic facelift thyroidectomy' [5]. Later cadaver study case series and original articles were reported in the literature [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%